2005
DOI: 10.1177/104063870501700620
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Necrotizing Fasciitis and Myositis in a Captive Common Bottlenose Dolphin (Tursiops Truncatus) Associated with Streptococcus Agalactiae

Abstract: Abstract.A common bottlenose dolphin (Tursiops truncatus) was presented for necropsy after acute onset of gastrointestinal signs and cutaneous lesions that rapidly progressed to death. Gross and microscopic findings were characterized by locally extensive severe necrohemorrhagic fasciitis and cellulitis, and severe necrotizing myositis in the head and dorsocranial thorax, with numerous disseminated gram-positive cocci. Streptococcus agalactiae was isolated from the lesions and from visceral organs (liver and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 22 publications
0
36
0
2
Order By: Relevance
“…This organism has also been identifi ed in aquatic mammals, both captive and wild bottlenose dolphins (Tursiops truncatus) (2,3). GBS causes mastitis in cattle and meningitis in human neonates (4).…”
Section: S Treptococcus Agalactiae Group B Streptococcus (Gbs)mentioning
confidence: 99%
“…This organism has also been identifi ed in aquatic mammals, both captive and wild bottlenose dolphins (Tursiops truncatus) (2,3). GBS causes mastitis in cattle and meningitis in human neonates (4).…”
Section: S Treptococcus Agalactiae Group B Streptococcus (Gbs)mentioning
confidence: 99%
“…In a stranded pygmy killer whale (Feresa attenuata), a low serum ALP value suggested that the animal may have been suffering from a critical illness. 26 Although a higher CK value usually indicates severe necrotizing muscles lesions, 5,36 subnormal CK value is sometimes associated with myopathy, muscle wasting, cachexia, or corticosteroid therapy. 14,27 Based on the hematological findings, a presumptive diagnosis of muscle damage was made in the present study.…”
mentioning
confidence: 99%
“…6 Severe streptococcal cellulitis associated with septicemia or toxic shock syndrome is rare, especially in veterinary medicine, but outbreaks due to Streptococcus canis have been described in dogs and cats, and Streptococcus agalactiae and Streptococcus pneumoniae were respectively cultured from a bottlenose dolphin and a kitten with cellulitis and septicemia. 9,11,20,21 Cellulitis has rarely been described in the bovine species. 1,12,13 In this species, it is often associated with Clostridium spp.…”
mentioning
confidence: 99%
“…Moreover, although the classic cases described in the 1990s involved exclusively group A streptococci (GAS), b-hemolytic groups B, C, and G streptococci have also been involved in several human and animal cases of TSS and/or necrotizing fasciitis. 5,20 For example, in 1 study, 21 human isolates of invasive S. dysgalactiae subsp. equisimilis were screened for the presence of 6 superantigens genes often found in cases of GAS TSS.…”
mentioning
confidence: 99%